The oldest sports library in the world celebrates 200 years - Haglund, Lotta; Ekenberg, Anna; Jäppinen, Karin; Karlsson, Heléne (Journal of EAHIL, 2017)
The article relates the 200 year history of the Swedish School of Sport and Health Sciences in Stockholm, Sweden, fromÂ its founder, Pehr Henrik Ling to its present status as the oldest sports library in the world. The authors describe theÂ library’s humble beginnings to its important role nowadays as an integral part of the School’s sport educationÂ curriculum.